Automation trends and labor markets in Latin America - Irene Brambilla; Andrés César; Guillermo Falcone; Leonardo Gasparini (Inter-American Development Bank (IDB), 2023)
This paper studies the effects of automation of production on labor market outcomes, and whether there is an effect of automation on functional and personal inequality in Latin America. The paper combines several data sources and empirical strategies in order to approach the issues from different perspectives and to cover different dimensions of labor markets. The main issues that we focus on are: i) the hypothesis that industries with a higher share of workers performing routine tasks are more likely to be affected by automation, using indexes of task routinization by occupation; and ii) the effects of automation on industry and local labor share, employment, wages, personal inequality and poverty. We focus on seven Latin American countries: Argentina, Brazil, Chile, Colombia, Ecuador, Mexico and Peru, during the period 1992-2015.
Keywords: J21; J24; O33; 330; automation; labor share; labor markets; functional inequality; personal inequality; Latin America